Don’t Let a Crisis Go to Waste : Reshaping the Economy through ‘No-Regret’ Policies - World Bank (World Bank, Washington, DC, 2020)
Vietnam has the unique opportunity to take advantage of the COVID-19 crisis. While the future is hard to predict, most would agree that the world will look very different in the post coronavirus era. There will be a notable reshaping of global value chains. Similarly, the development of contact-free services, telemedicine, and e-commerce will accelerate requiring fast adaptation of existing digital systems. Lastly, the importance and value of human life will increase as more governments prioritize the inclusion of the wellbeing of future generation in policy making. The ongoing transformation of the global economy provides the opportunity for Vietnam to take important policy actions and move faster toward its goal of becoming a high-income economy. We recommend five concrete pathways on which Vietnam can build on: tapping into the new global trading system, promoting digital payments for a new business model, promoting telemedicine, enhanced information sharing for increased resilience, and aiming for a low-carbon economy.